206k views
21 votes
PLEASE HELP ASAP PLEASE THANK YOU

PLEASE HELP ASAP PLEASE THANK YOU-example-1

1 Answer

7 votes

m∠A + m∠B = m∠B + m∠C

Example: Δ ABC is isosceles at B

⇒ m∠A = m∠C

⇔ m∠A + m∠B = m∠B + m∠C

So: m∠A + m∠B = m∠B + m∠C ⇒ m∠A = m∠C

P/s: sorry, my writing skill is not very good, but u can use the above ideas to write

Ok done. Thank to me :>

PLEASE HELP ASAP PLEASE THANK YOU-example-1
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.